2002
DOI: 10.1111/1467-9450.00278
|View full text |Cite
|
Sign up to set email alerts
|

Negative affect and sensitization to pain

Abstract: Pain usually has a strong negative affective component, which is believed to modulate pain perception. After reviewing theories on the link between negative affect and pain, mechanisms are discussed by which negative affect may either increase or inhibit pain. Possible pain-inhibiting mechanisms are endogenous opioid release, blood pressure reactivity, and distraction of attention; possible pain-increasing mechanisms are autonomic and muscular reactivity, misattribution of arousal, hypervigilance to pain, worr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
2
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 80 publications
1
82
2
7
Order By: Relevance
“…A previous study has shown that anxiety increases pain sensation. 46 Unfortunately, diazepam or its combination with the nonopioids analgesics mentioned above failed to demonstrate the effectiveness against PRP-associated pain in our study. Of note, although our study has shown that oral or intramuscular NSAIDs are not effective for PRP-associated pain, topical NSAID has been reported to be effective in reducing PRP-induced pain.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…A previous study has shown that anxiety increases pain sensation. 46 Unfortunately, diazepam or its combination with the nonopioids analgesics mentioned above failed to demonstrate the effectiveness against PRP-associated pain in our study. Of note, although our study has shown that oral or intramuscular NSAIDs are not effective for PRP-associated pain, topical NSAID has been reported to be effective in reducing PRP-induced pain.…”
Section: Discussioncontrasting
confidence: 59%
“…Previous research has found that possible pain-inhibiting mechanisms that are endogenous opioid release, blood pressure reactivity, and distraction of attention; possible pain-increasing mechanisms are autonomic and muscular reactivity, misattribution of arousal, hypervigilance to pain, worrying, and avoidance behaviour. 46 Therefore, measures to promote paininhibiting mechanisms or decrease pain-increasing mechanisms may help reduce patients' painful sensation during PRP treatment. Use of some psychological interventions, such as positive emotion induction or relaxation procedures, was found useful for acute pain management.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, at the level of individual variation within lines, higher amounts of running tend to be weakly associated with shorter tailflick latencies (increased pain sensitivity). Note that this is contrary to the prediction that the acute effect of exercise decreases pain sensitivity [3][4][5][6][7].…”
Section: Experiments Icontrasting
confidence: 66%
“…[1,2]). In contrast, studies in both rodents and humans have demonstrated that exercise can also reduce pain [3][4][5][6][7]. The phenomenon in which pain perception is altered during exposure to various stressors has been referred to as stress-induced analgesia, or specifically as exercise-induced analgesia when physical activity is involved.…”
Section: Introductionmentioning
confidence: 99%
“…Rhudy and Meagher (2001b) speculated that negative emotions of low to moderate intensity increase attention towards and amplify pain via neural circuits in the amygdala and periaqueductal grey that also modulate startle responses. Alternatively, an increase in the concentration of circulating catecholamines during psychological stress (Janssen et al, 1998), or selective attention or misattribution of arousal (Janssen, 2002), might heighten sensitivity to pain. Anger is generally associated with hyperalgesia (Bruehl et al, 2002;Janssen, Spinhoven, and Brosschot, 2001), possibly for similar reasons.…”
Section: Discussionmentioning
confidence: 99%